2011
DOI: 10.1186/1475-2875-10-300
|View full text |Cite
|
Sign up to set email alerts
|

A simple and fast method to exclude high Plasmodium falciparum parasitaemia in travellers with imported malaria

Abstract: BackgroundCounts of malaria parasites in peripheral blood are important to assess severity of Plasmodium falciparum malaria. Thin and thick smears are routinely used for this purpose.MethodsIn this study the Binax NOW® Malaria Test, an easy-to-perform rapid diagnostic test, with Histidine Rich Protein-2 (HRP-2) and aldolase as diagnostic markers, was used for semi-quantitative assessment of parasitaemia of P. faciparum.ResultsIn 257 patients with imported P. falciparum malaria, reactivity of aldolase increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
1
4
0
1
Order By: Relevance
“…We have demonstrated that the BinaxNOW commercial RDT and a validated qPCR based on the Plasmodium 18S rRNA region were unable to differentiate asexual from sexual stages of P. falciparum , however, the presence of the pan- Plasmodium aldolase T2 band was correlated to both higher parasitemia by microscopy and 18S rRNA gene copy number. This latter finding is consistent with previous research in which the absence of the aldolase T2 band served as a reasonable basis on which to rule out high parasitemia [ 19 ]. Although RNA transcript expression of eba-175 had a low positive predictive value (62.5 %) in this study, it provided a negative predictive value of 100 % for asexual stages, suggesting that it is potentially a good marker to rule-out asexual parasitemia in specimens received at the laboratory.…”
Section: Discussionsupporting
confidence: 92%
“…We have demonstrated that the BinaxNOW commercial RDT and a validated qPCR based on the Plasmodium 18S rRNA region were unable to differentiate asexual from sexual stages of P. falciparum , however, the presence of the pan- Plasmodium aldolase T2 band was correlated to both higher parasitemia by microscopy and 18S rRNA gene copy number. This latter finding is consistent with previous research in which the absence of the aldolase T2 band served as a reasonable basis on which to rule out high parasitemia [ 19 ]. Although RNA transcript expression of eba-175 had a low positive predictive value (62.5 %) in this study, it provided a negative predictive value of 100 % for asexual stages, suggesting that it is potentially a good marker to rule-out asexual parasitemia in specimens received at the laboratory.…”
Section: Discussionsupporting
confidence: 92%
“…Reactivity with the aldolase antibody would not be unexpected with P. falciparum, as aldolase is a panmalarial antigen; however, the absence of HRP-2 reactivity is puzzling. A recent report described a positive association between P. falciparum parasitemia and coreactivity of aldolase and HRP-2 in the BinaxNOW test (18). Given that the parasitemia was not high, a prozone effect is unlikely to explain this phenomenon.…”
Section: Discussionmentioning
confidence: 94%
“…The standard procedure to diagnose malaria comprised a quantitative buffy coat (QBC) analysis, a rapid diagnostic test (RDT) for malaria antigens (Binax NOW ® Malaria Test Binax, Inc, Maine, USA), and thick and thin blood smears using freshly collected blood specimens from finger pricks. The RDT and the QBC analysis were performed according to the manufacturer’s instructions [ 23 , 24 ]. QBC capillaries were examined independently by two technicians by microscopic analysis of two complete rows of the region between the bottom of the capillary and the polynuclear leukocyte layer using an Olympus BX-60 fluorescence microscope equipped with UV-filter, 50× objective and 12.5× oculars (total magnification 625×).…”
Section: Methodsmentioning
confidence: 99%